Instructions about the structure of manuscript of Revista Cátedra - Simbaña-Gallardo, Verónica (2021)
This article aims to explain the presentation, structure and submission of the manuscript to Revista Cátedra. The instructions are of obligatory use so that the article complies with quality standards and indexing. The journal is aligned with the IMRAD structure, which stands for the four sections of an article: introduction, materials and methods, results and discussion Although the IMRAD format only includes the body of the article there are other important aspects that should be considered, such as: topic, authors, abstract, keywords, literature review, acknowledgment (optional) and references. In this article each component of the manuscript is detailed in a clear, descriptive, concise way and easy to understand. The instructions presented in this article aim to improve the scientific writing of the manuscript to guarantee its publication, since the manuscript is the most effective means that a researcher has to show his/her work and the results of an investigative process. Revista Cátedra has as theoretical bases the Education Sciences in its different specialties and educational levels; based on these principles and the reflection of the teaching practice, it will publish original, innovative and strategic articles to strengthen the improvement of the educational process and its linkage with the scientific community.